Population study of Cucurbita moschata based on morphological characters and isozyme banding patterns in Bima District, West Nusa Tenggara, Indonesia - MUHAMMAD FURQAN; SURANTO SURANTO; SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2024)
Abstract. Furqan M, Suranto, Sugiyarto. 2023. Population study of Cucurbita moschata based on morphological characters and isozyme banding patterns in Bima District, West Nusa Tenggara, Indonesia. Biodiversitas 25: 30-38. Pumpkin is a tropical plant that benefits from its lipid, protein, carbohydrate, and mineral contents. The morphological characters of pumpkins can be influenced by their genetics and environment. This research aimed to examine the relationship among 9 accessions of Cucurbita moschata Duchesne from 9 locations in Bima district, West Nusa Tenggara (NTB) province, Indonesia. The morphological characters of stems, leaves, and flowers were analyzed qualitatively and quantitatively and an ANOVA was used to look at the difference of leaf and flower characters. Polyacrylamide gel electrophoresis (PAGE) with peroxidase and esterase was used to detect isozyme banding patterns. Morphological characters and isozyme data were analyzed using a UPGMA method with NTSYS version 2.0 software to construct a dendrogram. The results show evidence of the varied morphological appearance of C. moschata from the different locations. A total of 12 esterase bands and 10 peroxidase bands were detected from Wera2. An undetected band with Rf value of 0.567 was recorded, while a unique band with Rf value of 0.133 (peroxidase) was not detected. Undetected bands with Rf values of 0.645 and 0.726 of esterase were also recorded. A dendrogram showed three clusters of 9 accessions studied, in which Wera2 and Wera3 each stood alone, and a third large group was formed from the 7 remaining accessions. These results confirm the uniqueness of the Wera2 and Wera3 accessions. These results would be good information in determining a management strategy for improving the quality of pumpkins in the future.